Change of Logarithm Base

🏆Practice change-of-base formula for logarithms

Change of Logarithm Base

Reminder - Logarithms

The definition of the logarithm:
logax=blog_a⁡x=b
X=abX=a^b

Where:
aa is the base of the log
XX is what appears inside the log - can also appear inside of parentheses
bb is the exponent to which we raise the base of the log in order to obtain the number that appears inside of the log.

How to change the base of a logarithm?

According to the following rule:
logaX=logthe base we want to change toXlogthe base we want to change toalog_aX=\frac{log_{the~base~we~want~to~change~to}X}{log_{the~base~we~want~to~change~to}a}

In the numerator there will be a log with the base we want to change to, as well as what appears inside of the original log.
In the denominator there will be a log with the base we want to change to, and the content will be the base of the original log.

Start practice

Test yourself on change-of-base formula for logarithms!

einstein

\( \frac{\log_85}{\log_89}= \)

Practice more now

Change of Logarithm Base

Logarithm - Reminder

First, let's recall the definition of the log and understand what is the base of a logarithm:

The definition of the logarithm is:
logax=blog_a⁡x=b
X=abX=a^b

Where:
aa is the base of the log
XX is what appears inside the log - which can also appear inside of parentheses
bb is the exponent to which we raise the base of the log to in order to obtain the number that appears inside of the log.

The rule states that if we raise base aa to the power of bb we obtain XX.
In order to solve a log, we ask ourselves - to what power should we raise aa to obtain XX.
The power bb that we found is the solution.

For example:
When we have the expression
log525=log_5⁡25=

Let's ask ourselves –
To what power do we need to raise 55 to in order to obtain 2525? The answer is 22. Therefore:
log525=2log_5⁡25=2


Important to know - the log in the example is read as follows:
log base 55 of 2525

Change of logarithm base

You're probably asking yourself, why do we need to change the base of the logarithm?
Excellent question!
Sometimes in subtraction, addition, multiplication, or division exercises with different bases, it is easier for us to change the base of one of the logarithms so we can use the addition and subtraction formulas, and the same goes for multiplication and division.
So how do we do it? According to the following rule:

The Change of Base Rule for Logarithms:

logaX=logbase we want to change toXlogbase we want to change toalog_aX=\frac{log_{base~we~want~to~change~to}X}{log_{base~we~want~to~change~to}a}

Let's look at an example:
Here is the exercise:
log816=log_8⁡16=
Convert it to a log with base 22.

Solution:
Upon observation this is an illogical solution... To what power should we raise 88 to in order to obtain 1616?
Therefore, we can change the base of the log and solve the problem far more easily! Note that the instruction is to change the log to base 22.
To change the base of the log, we'll use the formula:
In the numerator, we'll have log base 22 (the base we want to change to) with the original log content 1616
And in the denominator, we'll have log base 22 (the base we want to change to) with 88 the original base.
We obtain the following:
log816=log216log28log_8⁡16=\frac{log_2⁡16}{log_2⁡8 }
Are we done? Not yet. Now we must proceed to solve the logs until we obtain a number.
log216=4log_2⁡16=4
log28=3log_28=3
We insert the data into the exercise as seen below to obtain our solution:
=43=\frac{4}{3}
Amazing!

Now we'll increase the difficulty level and move on to another exercise with a variable where we'll also use the change of logarithm base rule:
log6x+log36x=3log_6⁡x+log_{36}⁡x=3

Solution
First of all, don't panic. With the rule you just learned, you can solve this exercise very simply. Let's start step by step.

When encountering two logarithms with different bases, the first step is to convert the larger log to the smaller one because it will be simpler to solve.
Let's do it - we'll convert log36xlog_{36}⁡x to base 66 and get:
log36x=log6xlog636log_{36}⁡x=\frac{log_6x}{log_6⁡36 }

Insert the data into the exercise as follows:

log6x+log6xlog636=3log_6⁡x+\frac{log_6⁡x}{log_6⁡36} =3

Let's continue solving the exercise.
We can solve the denominator -
log636=3log_6⁡36=3
Insert into the exercise
log6x+log6x2=3log_6⁡x+\frac{log_6⁡x}{2}=3〗
Let's continue solving the problem and write the exercise in a simpler form:

log6x+0.5log6x=3log_6⁡x+0.5 log_6⁡x=3
Let's combine like terms:
1.5log6x=31.5 log_6x=3

log6x=2log_6 x=2
Solve the following –
x=62x=6^2
x=36x=36

Tip - Sometimes it's useful to substitute an auxiliary variable tt instead of the entire log.
When reached this stage in the exercise -
log6x+log6x2=3log_6⁡x+\frac{log_6⁡x}{2}=3
We can substitute
log6x=tlog_6 x=t
as follows:
t+t2=3t+\frac{t}{2}=3
1.5t=31.5t=3
t=2t=2

But notice, this is not the result. Now we need to substitute 22 instead of tt
and determine xx
we obtain the following solution :
log6x=2log_6 x=2
62=x6^2=x
x=36x=36

Join Over 30,000 Students Excelling in Math!
Endless Practice, Expert Guidance - Elevate Your Math Skills Today
Test your knowledge

Examples with solutions for Change-of-Base Formula for Logarithms

Exercise #1

log85log89= \frac{\log_85}{\log_89}=

Video Solution

Answer

log95 \log_95

Exercise #2

log4x9log4xa= \frac{\log_{4x}9}{\log_{4x}a}=

Video Solution

Answer

loga9 \log_a9

Exercise #3

log89alog83a= \frac{\log_89a}{\log_83a}=

Video Solution

Answer

log3a9a \log_{3a}9a

Exercise #4

log9e2log9e= \frac{\log_9e^2}{\log_9e}=

Video Solution

Answer

2 2

Exercise #5

log74= \log_74=

Video Solution

Answer

ln4ln7 \frac{\ln4}{\ln7}

Start practice